WORKSHOP INTERNET OF THINGS MAHASISWA PROGRAM STUDI MANAJEMEN INFORMATIKA UNIVERSITAS MERDEKA MADIUN - Sukadi (Universitas Merdeka Madiun, 2025)
Internet of Things technology has now become a trend or is widely used to meet the needs of life or lifestyle of the community. To prepare students to face the trend in society, an Internet of Things workshop was held with the theme